Tax Culture as a Determining Factor in Property Tax Collection: A Correlational Study in a Local Government of Peru - Gonzáles Alcedo , Jaime Stiven (2026)
The purpose of this research was to determine the relationship between tax culture and property tax collection in the Provincial Municipality of Sullana, Peru. A quantitative, basic- type methodology with a non-experimental, correlational design was used. The sample consisted of 87 employees from the municipality's Tax Administration Management. Two questionnaires, one for each variable, were administered, validated by expert judgment and showing high reliability (Cronbach's Alpha > 0.8). The results revealed a Pearson correlation coefficient of 0.743 (p < 0.01), indicating a positive and high relationship between tax culture and property tax collection.   It is concluded that strengthening tax culture, especially in its informational, motivational, and operational dimensions, is fundamental to improving collection levels. Tax education and effective communication about the use of public funds are key strategies to encourage voluntary compliance with tax obligations and, consequently, local development.